Quantum wreath products and Schur–Weyl duality I - Chun-Ju Lai; Daniel K. Nakano; Ziqing Xiang (Forum of Mathematics, Sigma, 2024)
In this paper, the authors introduce a new notion called the quantum wreath product, which is the algebra